PEMETAAN HEC-RAS 2D UNTUK ANALISIS SPASIAL RISIKO BANJIR BERBASIS DATA TOPOGRAFI (LOKASI : DESA FAHILUKA, KABUPATEN MALAKA, NTT) - Bees, Azarya; Ildo Rivendi Naikofi, Mauritius; Satrio Wibowo Pedo, Krisantus; Mooy, Merzy (JURNAL TEKNIK SIPIL, 2025)
The risk of damage due to flooding can be prevented by mapping the area or scope of flood inundation. Flood characteristics in the form of inundation area, inundation depth and flow velocity need to be mapped so that they can become the basis for flood control planning. This research aims to analyze the level of flood vulnerability in Fahiluka village based on the characteristics of the floods that occur. Hydrological analysis shows a trend of increasing rainfall over the last 12 years due to the impact of global climate change. The results of flood simulations for return periods of 25, 50 and 100 years using Hec-Ras 2D version 5.0.7 software show that the area of the village that has the potential to be inundated is 500 ha, 750.29 ha; 1020 ha with flood depths varying between 0.5 m 4.25 m with medium-high hazard categories.